General Pharmacology of the New Antiviral Agent SK 1899 - Ryu, Keun Ho; Rhee, Hae In; Jung, Inho; Kim, Taek-Soo; Lee, Sung Jae; Im, Guang-Jin; Lee, Namkyu; Ryu, Do Hyun; Kim, Young-Woo; Kim, Jae-Jun; Chang, Kieyoung; Lee, Byung Ho; Shin, Hwa Sup; Kim, Eun-Joo; Kim, Key H; Kim, Dae-Kee (Arzneimittelforschung, 2000)
The general pharmacological properties of 2-amino-9-(3-acetoxymethyl-4-isopropoxycar-bonyloxybut-1-yl) purine (CAS 247081-81-8, SK 1899), a new potential antiviral agent, were investigated in mice, rats, guinea pigs, rabbits, and dogs. The oral administration of 50, 150, and 500 mg/kg of SK 1899 had no effects on the central nervous system except that it slightly increased the spontaneous locomotor activity in mice at a dose of 500 mg/kg. SK 1899 did not disturb either the spontaneous motility or contractor-induced contraction of the isolated organs such as guinea pig ileum, rat uterus, guinea pig vas deferens, and guinea pig trachea at concentrations up to 10–4 mol/l. It slightly increased the contractile force in the isolated guinea pig atrium at a concentration of 10–4 mol/1. Following intravenous infusion of 5, 15, and 50 mg/kg of SK 1899 to anesthetized dogs, it did not change the mean arterial pressure, heart rate, left ventricular systolic pressure (LVSP), and respiratory rate, while it slightly increased the left ventricular positive dP/dtmax (LV + dP/dtmax) at a dose of 50 mg/kg. SK 1899 did not induce any significant changes in the intestinal charcoal meal transit in mice, basal gastric juice secretion in rats, and renal function in rats. It did not affect the blood coagulation system and phenolsulfonphthalein secretion in rats. These findings suggest that SK 1899 has a very low potential to induce any adverse pharmacological effects at the doses showing antiviral activity.
Keywords: 2-Amino-9-(3-acetoxymethyl-4-isopropoxycarbonyloxybut-l-yl)purine; Antiviral agents; CAS 247081-81-8; SK 1899, general pharmacology